2022
DOI: 10.3390/ijerph191610233
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Camps as Torturing Environments—An Analysis of the Conditions in the Moria Reception Center (Greece) Based on the Torturing Environment Scale

Abstract: Background. European countries apply a policy of deterrence of migrants in territorial and extraterritorial border areas. The authors apply the model of torturing environments, which has been already applied to other contexts where persons are deprived of liberty, to the situation of the reception center of Moria, on the island of Lesvos (Greece). Methods. A cross-sectional study was conducted in the months of April and June of 2020. Personal interviews were conducted with 160 people (80 men, 80 women) from Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Participants sought help through different sources. In line with previous research [ 68 ] the interviews with females showed scepticism toward mental health professionals unfamiliar with their background. This might illuminate recent research showing that healthcare service utilization rates among refugees in camps are particularly low for common mental disorders [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…Participants sought help through different sources. In line with previous research [ 68 ] the interviews with females showed scepticism toward mental health professionals unfamiliar with their background. This might illuminate recent research showing that healthcare service utilization rates among refugees in camps are particularly low for common mental disorders [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…We collected data on violence occurring in 44 different countries, grouped by region: Europe [ 22 , 62 , 65 , 68 , 81 , 91 ]; North America [ 64 , 67 , 69 , 72 , 74 , 75 , 78 , 80 , 82 , 85 ]; Asia [ 31 , 76 , 87 ]; and Africa [ 70 , 71 , 77 , 84 , 86 , 88 ]. Twenty-five of the included reports measured violence in a single country [ 64 , 65 , 67 , 69 , 70 72 , 74 , 75 , 77 , 78 , 81 , 82 , 84 89 , 91 , 93 , 94 ]. The remaining reports either specified a combination of locations in which the violence occurred or specified that the violence happened while in transit during the migration journey.…”
Section: Resultsmentioning
confidence: 99%
“…Studies measured insecure immigration status in a number of different ways. These included ‘undocumented’ [ 22 , 64 67 , 69 , 72 , 74 , 75 , 77 , 80 82 , 85 , 89 ], ‘refugee /asylum seeker’ [ 62 , 63 , 68 , 70 , 71 , 73 , 83 , 84 , 86 88 , 90 , 91 ], ‘spousal /family visa’, ‘employment related’ [ 31 , 76 , 79 ]. Two studies measured more than one status but sufficiently disaggregated the data to allow for insecure status to be verified [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the underlying mechanism would not be an increased willingness to take risks, but rather a higher level of confidence in one's own (physical) abilities. A further alternative explanation could be that being stuck in a refugee camp is a frustrating (and sometimes traumatising) experience 82 , 83 . Since in Greece camp residents are not given the opportunity to pursue a gainful employment, the level of frustration might be particularly pronounced among residents who feel strong and fit.…”
Section: Discussionmentioning
confidence: 99%